Anaphylactic shock during SpaceOAR Vue hydrogel procedure - Lauren Nesi; Paramjot Gogia; Aishwarya Navalpakam; Nitin Vaishampayan; Conrad Maitland (Urology Case Reports)
In this report, we present a unique and rare case of an intraoperative anaphylactic shock leading to cardiac arrest during the SpaceOAR Vue™ hydrogel procedure in a 70-year-old patient undergoing External Beam Radiation Therapy (EBRT) for advanced localized prostate cancer. To our knowledge, this is the first urologic case report documenting this adverse reaction associated with the placement of the SpaceOAR Vue product. We discuss the possible culprits, including the hydrogel's polyethylene glycol (PEG) and iodine content, perioperative antibiotics, and local lidocaine anesthetic, and propose relevant considerations for clinicians administering rectal hydrogel spacers.